1997
DOI: 10.1139/v97-042
|View full text |Cite
|
Sign up to set email alerts
|

Electronic absorption spectra and structure of hydroxycoumarin derivatives and their ionized forms

Abstract: Electronic absorption spectra of 18 hydroxycoumarin derivatives and their ionized forms have been studied. Close agreement between experimental and the PPP CI calculated electron absorption band energies has been found in most cases. Strong polarization of the carbonyl function of the pyrone ring in the 7-hydroxycoumarin derivatives, H-bonding between the hydroxyl group and neighboring substituent in the ortho-substituted hydroxycoumarins, as well as their tautomeric transformations, have been suggested in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…On the other hand, condensation of 2-hydroxyacetophenone 5 with trichloroacetonitrile in the presence of N-methylanilinomagnesium bromide afforded (Z)-3-amino-4,4,4-trichloro-1-(2-hydroxyphenyl)but-2-en-1-one 7, which was converted into 2-(trichloromethyl)chromones 8 upon treatment with concentrated hydrochloric acid. The base catalyzed hydrolysis of the later compound gave 4-hydroxycoumarin 1 (Traven et al, 1997b) (Scheme 3). Scheme 6.…”
Section: Using 2-hydroxyacetophenonementioning
confidence: 99%
“…On the other hand, condensation of 2-hydroxyacetophenone 5 with trichloroacetonitrile in the presence of N-methylanilinomagnesium bromide afforded (Z)-3-amino-4,4,4-trichloro-1-(2-hydroxyphenyl)but-2-en-1-one 7, which was converted into 2-(trichloromethyl)chromones 8 upon treatment with concentrated hydrochloric acid. The base catalyzed hydrolysis of the later compound gave 4-hydroxycoumarin 1 (Traven et al, 1997b) (Scheme 3). Scheme 6.…”
Section: Using 2-hydroxyacetophenonementioning
confidence: 99%
“…The structure of 3-acetyl-4-hydroxycoumarin has been assigned by UV (Klutchko et al, 1974;Traven et al, 1997), IR (Naceur et al, 2011;Eiden and Rademacher, 1983;Babin et al, 1981), MS (Naceur et al, 2010;Fischmeister et al, 2011;Sukdolak et al, 2004), NMR (Li et al, 2012a;Athanasellis et al, 2004;Kravchenko et al, 1999), fluorescence (Li et al, 2012a) and photoelectron (Traven et al, 2000) spectroscopy. The UV-Vis absorption and photoluminescence spectra of 3-acetyl-4-hydroxycoumarin in dilute dichloromethane solutions revealed a sharp absorption peak at 300 nm, with a shoulder at 341 nm (Li et al, 2012a).…”
Section: Molecular Structures and Spectral Propertiesmentioning
confidence: 99%
“…3). These possible prototropic transformations have been investigated experimentally by UV spectroscopy and theoretically by the semi-empirical and non-empirical quantum chemical calculations (Traven et al, 1997(Traven et al, , 2000Stanovnik et al, 2006;Lyssenko and Antipin, 2013). According to these studies, 3-acetyl-4-hydroxycoumarin mainly exists in endocyclic enol form (B) in solid states.…”
Section: Tautomeric Structure (S)mentioning
confidence: 99%
“…At the same time, the calculation results often depend on the adequate choice of atomic and bond parameters. Earlier, 15 we have shown that the reliability of analysis of such systems is determined by the objectivity of taking account of intramolecular hydrogen bonding and molecule geometry.…”
mentioning
confidence: 99%